Application of Poly(ether sulfone)‐Based Membranes in Clean Energy Technology. Issue 1 (26th November 2022) - Shi, Dingqing; Li, Chunyang; Yin, Yanbin; Lu, Wenjing; Li, Guojun; Li, Xianfeng
Abstract: Poly(ether sulfone) (PES) is a kind of polymer materials with excellent electrical insulation and acid/alkali stability. PES can be operated at high temperature continuously for a long time and still maintain excellent property stability in the environments with rapidly changed temperature, namely, great thermostability. Moreover, PES has low molding shrinkage, good dimensional stability and excellent film‐forming characteristics. Compared with inorganic membranes, PES‐based membranes have lower cost, which have received more attention and wide recognition in the field of clean energy technologies in recent years, such as flow batteries, fuel cells, water treatment, and gas separation. Therefore, this review summarizes the research status and prospect of the utilization of PES‐based membranes in clean energy fields, in order to further promote their development and application. Abstract : Poly(ether sulfone) (PES) has a good molecular stability, excellent mechanical and film‐forming properties, and is very suited for clean energy storage technologies. This review summarizes the research process of PES‐based membranes in clean energy fields, mainly including strategies of membrane composition/structure regulation and performance increase. The application prospect of PES‐based membranes in different clean energy fields is also provided.